Global View of Animal Feed in Halal Perspective - Rahim , Syed Fazal ur; Bin Masood , Muhammad Abdullah (International Journal of Halal Research, 2023)
Islamic concept of food consumption for human beings is derived from the term Tayyib which depicts both food safety and quality. Unlike the humans, though animals are not bound to any code of practice, yet with reference to the food animals their diet seeks the attention of Islamic jurisprudence. Animal feed is the preliminary Halal control point in Halal food supply chain when the matter comes to the animal derived ingredients. This paper aims to put forth a global view of animal feed in Halal perspective by showcasing firstly the global scenario of feed industry, feed compositions, hazards, and regional regulations, secondly by highlighting the Halal and Tayyib integrity concerns over different feed compositions and addressing them through the global Halal standards and Islamic rulings issued by various Halal industry players. This research presents an interdisciplinary work of Islamic jurisprudence and feed science, which intertwines research on global feed compositions and the fundamental requirements of Halal and Haram jurisprudence. Animals are not the addressees of Quran and Sunnah; hence they are not bound to follow any code of religion. They are free to live and consume the way they like; in addition, Islam holds mankind responsible for their welfare and rights. Animal feed becomes an important subject for Islamic Jurisprudence only when the matter comes to the food animals. With reference to the food animals, animal feed is the preliminary control point of food supply chain, hence, it must be from halal source and must not cause harm to the human health.